Assembly of Nano-Biocatalyst for the Tandem Hydrolysis and Reduction of p-Nitrophenol Esters - Barros, HR; Tanaka, LY; da Silva, RTP; Santiago‐Arcos, J; Torresi, SIC; López‐Gallego, F. (Particle & Particle Systems Characterization, 2021)
Hybrid nano-biomaterials are exploited in the design and performance of chemo-enzymatic cascades. In this study, lipase is immobilized from Candida antarctica fraction B (CALB) and gold nanoparticles (Au NPs) on magnetic particles coated with silica (MNP@SiO2) to stepwise hydrolyze and reduce p-nitrophenyl esters in tandem reaction. The assembly of the two catalysts at the interface of the MNP@SiO2 particles and the temporal control of the reaction turns out to be the most determinant parameters for the cascade kinetics. When both CALB and Au NPs are co-immobilized at the MNP@SiO2 particle, the tandem reactions take place significantly faster than when both catalysts are physically segregated by their immobilization on different MNP@SiO2 particles. Herein, it is demonstrated that the co-immobilization of biocatalysts and nanocatalysts in solid materials creates hybrid interfaces that accelerated chemo-enzymatic tandem reactions.